2004
DOI: 10.1016/j.jacc.2004.05.073
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of sudden cardiac death after mustard or senning repair for transposition of the great arteries

Abstract: Presence of symptoms and documented AFL/AF are the best predictors of SD in TGA patients. Patients with these findings should be further evaluated for risk of SD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
158
3
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 286 publications
(172 citation statements)
references
References 30 publications
(39 reference statements)
5
158
3
6
Order By: Relevance
“…This is in agreement with the concept of atrial arrhythmias being a marker of RV systolic dysfunction when assessed with nuclear imaging, as previously reported, and suggests that atrial arrhythmia in these patients is both a surrogate marker of ventricular dysfunction 22 and a predictor of death, as shown by Gewillig et al in 1991. 12 Our present data and the recent report by Kammeraad et al 24 imply that although these patients have the potential for fast 1:1 atrioventricular conduction, they probably die from ventricular tachycardia or ventricular fibrillation.…”
Section: Link Between Lge and Risk Factors For Arrhythmiasupporting
confidence: 60%
See 1 more Smart Citation
“…This is in agreement with the concept of atrial arrhythmias being a marker of RV systolic dysfunction when assessed with nuclear imaging, as previously reported, and suggests that atrial arrhythmia in these patients is both a surrogate marker of ventricular dysfunction 22 and a predictor of death, as shown by Gewillig et al in 1991. 12 Our present data and the recent report by Kammeraad et al 24 imply that although these patients have the potential for fast 1:1 atrioventricular conduction, they probably die from ventricular tachycardia or ventricular fibrillation.…”
Section: Link Between Lge and Risk Factors For Arrhythmiasupporting
confidence: 60%
“…21,22 Sudden cardiac death is the most common cause of late mortality in patients after Mustard or Senning operation. 11, 23 Kammeraad et al 24 recently reported that 8 such patients who had died suddenly with documentation of cardiac rhythm at the time, and 10 of 13 who had suffered near-miss sudden death, had either ventricular tachycardia or ventricular fibrillation. Experimental studies suggest that nonuniform recovery of ventricular excitability plays a role in the mechanism of ventricular arrhythmias.…”
Section: Link Between Lge and Risk Factors For Arrhythmiamentioning
confidence: 99%
“…SD in patients after atrial repair of TGA has been shown to be associated with prior episodes of IART and with symptoms of heart failure. (23) This reinforces the notion of a detrimental vicious circle with heart failure and atrial arrhythmias eventually leading to ventricular failure and SD. However, the possibility that IART with acute deterioration of ventricular function and development of VF is the cause of SD cannot be disproved.…”
Section: Referencessupporting
confidence: 70%
“…At the moment an anatomical correction is the most extensively used procedure; and the arterial switch has largely taken the place of the atrial switch procedure. Nonetheless late development of both atrial arrhythmias are well recognized late complications of atrial baffle surgery [4][5][6][7][8][9][10][11] (Table 1). Intra-atrial re-entrant tachycardia is the most common arrhythmia found among these patients, which has been associated with development of heart failure and death [5,9] .…”
mentioning
confidence: 99%
“…Nonetheless late development of both atrial arrhythmias are well recognized late complications of atrial baffle surgery [4][5][6][7][8][9][10][11] (Table 1). Intra-atrial re-entrant tachycardia is the most common arrhythmia found among these patients, which has been associated with development of heart failure and death [5,9] . In particular, causes of arrhythmias after the Mustard repair include [4,12,13] : (1) damage during surgery to the sinus node or sinus node artery; (2) break of intra-atrial conduction by interruption of internodal pathways; and (3) intraoperative damage to atrioventricular (AV) node conduction tissue.…”
mentioning
confidence: 99%